Results of some Trials with Eucalypts at Asarori, Dehra Dun - Qureshi, I. M. (Indian Forester, 1967)
In 1963, seven species of Eucalypts, viz., E. grandis, E. citriodora, E. gomphocephala, E. kirtoniana, E. tereticornis, E. rohusta, and E.hybrid (Mysore gum syn. E. tereticornis) were planted on a statistical design at Asarori, about 10 kilometres from F.R.I.,in an area which previously carried a coppice crop of Shorea robusta. The measurements taken in March, 1967, i.e., after 4Years, have indicated E.grandis to be fastest-growing with a M.A.I. of 22.138 m3/ha and an average diameter of 9.2 cm ond average height of 12.10 meters, the next best being E. citriodora with a M.AI.of 9.882 m3/ha, while E.hybrid (Mysore gum syn. E.tereticoris) gave a M.A.I. of only 3.15 m3/ha. As compared to Eucalypts, the M.A.I. of the coppice sa1 crop in the neighbourhood in Sample Plot Nos. 38 and 40 of Kansrao are 8.94 and 10.17 m3/ha respectively. Considering this E. grandis for this type of areas near Dehra Dun is the best choice in contrast to E.hybridand also local sal. These results also emphesise the great need for species trials for different climatic and edaphic zones to select best species, even among Eucalypts instead of raising E. hybrid at all place .